Bp44mT: An orally active iron chelator of the thiosemicarbazone class with potent anti-tumour efficacy - Yu, Yu; Rahmanto, Y.; Richardson, D. (John Wiley & Sons, 2012)
Background and Purpose: Our previous studies demonstrated that a thiosemicarbazone iron chelator (di-2-pyridylketone-4,4-dimethyl-3- thiosemicarbazone; Dp44mT) possesses potent and selective anti-cancer activity but led to cardiotoxicity at non-optimal doses. In this study, we examined the in vivo anti-tumour efficacy and tolerability of a new-generation 2-benzoylpyridine thiosemicarbazone iron chelator (2-benzoylpyridine-4,4- dimethyl-3-thiosemicarbazone; Bp44mT) administered via the oral or i.v. routes. Experimental Approach: BpT chelators were tested in vitro against human lung cancer cells (DMS-53) and in vivo in DMS-53 tumour xenografts in mice. The toxicity of Bp44mT in vivo and its effects on the expression of iron-regulated molecules involved in growth and cell cycle control were investigated. Key Results: Administration of Bp44mT by either route resulted in marked dose-dependent inhibition of tumour growth. When administered at 50 mg·kg -1 via oral gavage three times per week for 23 days, the net xenograft growth was inhibited by 75%, compared with vehicle-treated mice. Toxicological examination showed reversible alterations including slight reduction of RBC count, with a decrease of liver and splenic iron levels, which confirmed iron chelation in vivo. Importantly, in contrast to Dp44mT, the chelator-treated mice did not show cardiac histological abnormalities. There was also no significant weight loss in mice, suggesting oral administration of Bp44mT was well tolerated. Conclusions and Implications:This is the first study to show that Bp44mT can be given orally with potent anti-tumour efficacy. Oral administration of a novel and effective chemotherapeutic agent provides the benefits of convenience for chronic dosing regimens.